Increasing the Competence of Jayapura Regency’s Famers Through Training in Organic Fertilizer Production to Increase Plant Growth - Stephanny Inagama Timisela; La Maga -; Pisi Bethania Titalessy; Agustina Ester Antoh; Herlina Irianti Mulyono; Angga Frediyanto Palloan (Asia Pacific Journal of Management and Education (APJME), 2024)
The aim of this training is to increase the competence of farmers in Yobeh Village in terms of (1) farmers can utilize agricultural residues and organic waste; (2) farmers can reduce farming costs; and (3) farmers can produce environmentally friendly agricultural commodities. Training is carried out face to face so that farmers can carry out the stages of making organic fertilizer. Training activities were carried out in Yobeh Village, Sentani Kota District, Jayapura Regency. The tools and materials used in composting training consist of EM4 solution, water, forage or straw, husks, buckets, scoops, knives, or scissors. This training activity was carried out using lecture, training, and mentoring methods for participants. Based on the results of the training activities, it can be concluded: (1) The training participants had high enthusiasm and were proactive in asking several questions; (2) Basically, participants have used organic fertilizer in their farming activities, but have not used EM4 solution; and (3) Participants are able to understand the benefits, processes and materials used in making organic fertilizer. Suggestions that can be conveyed by the author include: (1) It is hoped that training participants will be able to utilize organic waste into organic fertilizer; and (2) Local regional governments are expected to provide training to improve farmer competency.